Shaka - Balogun, Lekan (Literamed Publications Nigeria Ltd, 2011)
He is destined to be a great leader but controversial circumstances surrounding his birth pose a big challenge to his mission,which he readily embraces as an inevitable avenue to actualize his fate.
Keywords: Drama; Historical; Nigeria(English); Shaka